Serials Spoken Here: Reports of Conferences, Institutes, and Seminars. Issue 2 (3rd April 2017) - Buck, Tina Herman; Church, Melanie J.; Foster, Anita; McHugh, Elizabeth; Robertson, Jessica; Rodriguez, Michael; Shenk, Audrey
ABSTRACT: This quarter's column spans nearly eight months in 2016 and comprises reports from three library conferences. The UKSG 39th Annual Conference and Exhibition took place in the Bournemouth International Center (BIC), April 11 to April 13. The Potomac Technical Processing Librarians 92nd Annual Meeting convened October 21 at the University of Richmond. The Charleston Conference took place in Charleston, SC, October 31 to November 5.